The impact of poorly controlled hypertension on ambulatory care resources in Malaysia - Abdul Razak, Tariq (2010)
Aim: Since many Malaysians with hypertension have poor control rates of blood pressure, this study wasconducted to determine the impact of uncontrolled hypertension on the utilization of ambulatory care resources. Setting: The study took place at the Jaya Gading Polyclinic in Kuantan city, Pahang, Malaysia.